Developed of the New Eight-legged Walking Bionic Robot - Zang Hongbin; Tao Junjie (Jixie chuandong)
A new kind of eight- legged walking bionic robot mechanical structure is designed. The kinematics equation of the leg is set up. Based on virtual prototyping technology,the mechanism of the bionic robot leg is optimized,and the ability of gradeability,crossing uneven road and the gait planning of the turning are simulated and analyzed. The results show that the eight- legged walking bionic robot has many excellent performances,including controlled easy,flexible movement,good climbing ability and small turning radius. Finally,a small physical prototype of the robot is developed,through which many excellent performances is tested.